Perbedaan Pola Konsumsi Asupan Zat Gizi dan Status Gizi Siswa SMAIT Al Uswah Surabaya Yang Tinggal di Asrama dan Non Asrama - Zafira Ananda Neda; Indrawati, Veni; Ismawati, Rita; Pratama, Satwika Arya (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2023)
Adolescence is a period of nutritional vulnerability caused by changes in lifestyle, eating habits, and physical activity. This study aims to determine the differences in consumption patterns, nutrient intake and nutritional status of SMAIT Al Uswah Surabaya students who live in dormitories and non-dormitories. This study applied a cross sectional research design involving 80 respondents, including 40 dormitory students and 40 non-dormitory students. Samples were selected using purposive sampling technique with statistical analysis of Mann Whitney test. Consumption patterns were measured through interviews using the food frequency questionare (FFQ), nutrient intake was measured through interviews using the 3x24 hours food recall questionnaire, and nutritional status measured through direct measurement of body weight and height. The results showed 1) There were differences in consumption patterns in staple food groups, animal side dishes, and fruits; while there were no differences in consumption patterns in vegetable side dishes and vegetables between dormitory and non-dormitory students of SMAIT Al uswah Surabaya. 2) There are differences in the intake of nutrients in the energy, protein, carbohydrate, vitamin A, vitamin C, iron, and zinc groups between boarding and non-dormitory students of SMAIT Al uswah Surabaya; while there are no differences in the intake of nutrients in the fat, vitamin B9, and calcium groups between boarding and non-dormitory students of SMAIT Al uswah Surabaya. 3) There are differences in the nutritional status of boarding and non-dorming students at SMAIT Al uswah Surabaya. The conclusion of this study is that there are differences in consumption patterns, nutrient intake, and nutritional status of SMAIT Al Uswah Surabaya students between those who live in dormitories and non-dormitories.